Value Stream Mapping implementation in Supply Chain Activities of SIGMA - ALDRICH family product at PT. ELO KARSA UTAMA - Ongko, Kelvin Marcus; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2015)
Abstract.Asian Economic Community (AEC) will bring the competition fiercer. Local companies must take step to enchance factors that drive their sustainability. One of the imperative factor from the operation side is the productivity. Productivity concerns regarding how well a company utilize its resource to transform into output or product . Lean manufacturing has become buzzword in business world to increase productivity, yet few had realized such concept had been extended beyond manufacturing, one is known as lean office. Value stream mapping plays as the foundation of lean journey. The idea of Value stream mapping is deconstruct the current state and reconstruct to future state in order to achieve better productivity. This paper take PT. ELO KARSA UTAMA, one of the leading distributing pharmacy in Indonesia. The company eager to have better operation productivty, therefore it install a ERP system a few years ago. Unfortunately company felt the achievement was not as supposed to be, thus open an opportunity for improvement. This project select SIGMA â€“ ALDRICH family product as the most complicated supply chain activity among others, as the chosen vendor to be work under the project. The current value stream shown the lean metrics that the current opeartion needs 9 people, 16 activity and 5986 minutes of total order lead time. Improvement was made by three area, office, warehouse and delivery. The improvement covers various departmetns that include logistic, sales, finance, data entry, warehouse and delivery. After seeking, analyzing and brainstrom the current process, the project reveals some major root cause through the fishbone. On each root cause the project try to offer some solution to fix the problem. Based on the proposed solution the new value stream mapping could be constructed and new lean metrics could be estimated. The new lean metrics shown as follows 6 people, 8 activity and 3676 minutes of total order lead time. Short term and long term recommendation also given beside the main recommendation. The real project implememntation will take five steps: Kick off meeting, construct project charter and template, training and awareness, implementation and closing meeting.Keywords: Asian Economic Community (AEC), value stream mapping, seven wastes, SAP, Lean ManufacturingÂ